Challenges of offering peace education among educational leaders: a case study of Malaysian public primary school - Khairuddin, Ahmad Zulfadhli; Abd Razak Al-Hafiz, Afareez; Idrus, Faizah; Ismail, Nik Ahmad Hisham (Center for Ethnic and Cultural Studies, Fort Myers, Florida United states of America, 2019)
This paper explores the challenges of offering peace education in public primary school in Malaysia. In exact, this study: first, investigates how school educational leaders perceive peace education and how peace education could be included in the school curriculum. This study has adopted a qualitative design, employing semi-structured interview as an instrument of data collection. Findings suggest that all respondents reported that they mutually agreed to include peace education as part of the curriculum to maintain harmony, inculcate tolerance among students, minimize conflicts and know their country’s history. Obstacles and challenges in introducing peace education as a subject in the school’s curricular can be minimized to implementation of costs and teacher training. Lack of expertise and lack of interests among students are identified as another challenge in introducing peace education. Furthermore, school educational leaders were found to have low levels of awareness, knowledge, and skills related to peace education.